Hubungan antara Peran Orang Tua dan Kemandirian Belajar Siswa kelas V SD Swasta di Airmadidi - Anita Amelia Ole; Ketlin Maradika (Journal on Education, 2024)
This research aims to determine how high the level of parental role and student learning independence is and whether there is a significant relationship between the role of parents and student learning independence. The results obtained show that to find out what level of role parents play in students, the statistical test results mean (M) = 4.27. From these results it can be seen that the role of parents for class V students at Airmadidi Private Elementary School is in the high category, meaning parents carry out their role well. Next, to find out the level of student learning independence in class, using statistical tests and obtaining a mean value (M) = 3.95, it can be interpreted that the level of student learning independence is classified in the high category, meaning students can independently carry out the tasks they get from school, and finally, namely to find out whether there is a significant relationship between the role of parents and students' learning independence in class V of Airmadidi Private Elementary School. The number of respondents in this study was 50 students and the correlation test results obtained between the role of parents and student learning independence were p value = 000 ≤ 0.05, indicating a relationship between the role of parents and student learning independence. Therefore, the hypothesis which states that there is no significant relationship between the role of parents and the learning independence of class V students at Airmadidi Private Elementary School, is rejected.